Pola Penyakit Dan Terapi Dengan Pendekatan Empirik Simptomatik Di Desa Gunung Sari - I Gede Yasa Asmara; Basuki Rahmat (Jurnal Gema Ngabdi, 2021)
The recent global economic crisis has resulted in more expensive health care in which, poor families might not get access to proper health care. Furthermore, global warming and pollution could influence change of disease patterns in the world, includes the tropical island of Lombok. For those two factors, it is interesting to know the disease pattern among poor people and also to give positive contribution for free medical care and treatment to them. A survey of disease patterns and free medical care had been done in Gunung Sari village in August 2015. Patient histories were taken using fundamental four and basic seven techniques whereas physical examinations were done by two registered general practitioners. Soon after working diagnosis is confirmed, empiric antibiotic treatment and symptomatic drugs are prescribed to the patients. As a result, 54% of 136 patients are male and 51,4% of them aged from 16 to 59 years old. Upper respiratory tract infections, diarrhea, and skin problems were the three common diseases. As for the empiric antibiotic treatment, Amoxycillin is the common agent used (34%). Moreover, antipyretic and anti-diarrhoea serve as the common symptomatic treatment used (21,3%). In a summary, the disease pattern and type of treatment given to poor people in Gunung Sari village were the same as that in other areas.